Anti‐LG3 Antibodies Aggravate Renal Ischemia–Reperfusion Injury and Long‐Term Renal Allograft Dysfunction. Issue 12 (23rd June 2016) - Yang, B.; Dieudé, M.; Hamelin, K.; Hénault‐Rondeau, M.; Patey, N.; Turgeon, J.; Lan, S.; Pomerleau, L.; Quesnel, M.; Peng, J.; Tremblay, J.; Shi, Y.; et al.
Abstract : Pretransplant autoantibodies to LG3 and angiotensin II type 1 receptors (AT1R) are associated with acute rejection in kidney transplant recipients, whereas antivimentin autoantibodies participate in heart transplant rejection. Ischemia–reperfusion injury (IRI) can modify self‐antigenic targets. We hypothesized that ischemia–reperfusion creates permissive conditions for autoantibodies to interact with their antigenic targets and leads to enhanced renal damage and dysfunction. In 172 kidney transplant recipients, we found that pretransplant anti‐LG3 antibodies were associated with an increased risk of delayed graft function (DGF). Pretransplant anti‐LG3 antibodies are inversely associated with graft function at 1 year after transplantation in patients who experienced DGF, independent of rejection. Pretransplant anti‐AT1R and antivimentin were not associated with DGF or its functional outcome. In a model of renal IRI in mice, passive transfer of anti‐LG3 IgG led to enhanced dysfunction and microvascular injury compared with passive transfer with control IgG. Passive transfer of anti‐LG3 antibodies also favored intrarenal microvascular complement activation, microvascular rarefaction and fibrosis after IRI. Our results suggest that anti‐LG3 antibodies are novel aggravating factors for renal IRI. These results provide novel insights into the pathways that modulate the severity of renal injury at the time of transplantation and their impact on long‐term outcomes. Abstract : Autoantibodies against LG3 are associated with delayed graft function and with its functional impact 1 year posttransplant in kidney transplant recipients, and aggravate renal microvascular damage and dysfunction in a murine model of renal ischemia–reperfusion injury.